Variações no teor de prolina livre em folhas destacadas de cinco cultivares de arroz (Oryza sativa L.) submetidas a desidratação - Madruga, L A N; Rena, A B (Revista Ceres, 2025)
Free proline concentration increased in detached leaves of five rice (Oryza sativa L.) cultivars subjected to water stress. The data suggest a threshold of water content in the leaves below which the metabolism is oriented toward proline synthesis. This threshold of water content in a apparently the same for all the cultivars studied. The leaves of the five cultivars lose water at different rates probably due to genetic differences among them. The younger turgid leaf tissues contain less free proline and accumulated more proline when subjected to water stress than did the older ones.